Impacts of School Communication on Job Satisfaction in Australian Primary Schools: A Structural Equation Model - De Nobile, John; Bilgin, Ayse Aysin (Frontiers in Education, 2022)
While there has been research into the ways some aspects of organizational communication may influence job satisfaction, it has not been comprehensive and very little work has been conducted in schools. This study investigates the influences of a comprehensive range of aspects of organizational communication on job satisfaction of school staff. Participants in the study were 1575 staff members from schools across Australia. A questionnaire survey was the primary instrument. Data were analyzed using exploratory and confirmatory factor analyses to validate constructs and multiple regression analyses, followed by structural equation modelling, to investigate effects. A ten factor model of aspects of organizational communication and six factor model of job satisfaction dimensions were identified and validated. Multiple regression analyses revealed that all ten aspects of organizational communication to have associations with job satisfaction. However, structural equation modelling revealed five aspects of organizational communication, to do with openness, support-giving, principal direction and participation in decision making to have the most important effects on job satisfaction. This study contributes to our knowledge of communication by confirming a ten factor model of organizational communication that can be used in other research. Implications for practice include the need for school leadership to foster open communication and facilitate school climates that encourage supportiveness, democracy and collegial direction.